Exploring the differences between sole silages of gramineous forages and mixed silages with forage legumes using 16S/ITS full-length sequencing - Lai, Xianjun; Wang, Haiyan; Yan, Junfeng; Zhang, Yizheng; Yan, Lang (Frontiers in Microbiology, 2023)
Silage characteristics of grass materials directly affect their silage qualities. To expand the source of silage raw materials and develop mixed silages underlined by exploring the positive interactions between forage grasses and legumes, three gramineous grasses, Napier grass (Pennisetum purpureum), king grass (Pennisetum sinese) and forage maize (Zea mays) were separately mixed ensiled with a combination of four forage legumes including Medicago sativa, Vicia villosa, Vicia sativa and Trifolium repens. The chemical composition, fermentation quality, and microbial diversity of the mixed silages were analyzed and compared with those of the sole silages of these three grasses. The results showed that the inclusion of forage legumes could somewhat improve the fermentation quality, as indicated by significantly (P < 0.05) higher crude protein and lactic acid contents while lower neutral detergent fiber, acid detergent fiber contents and pH values, compared with the sole silages. Among the three types of mixed silages, the mixed king grass had the highest dry matter and crude protein content as well as lowest neutral detergent fiber and acid detergent fiber content. Meanwhile, the bacterial and fungal communities in the mixed silages were influenced by increased the relative abundance of lactic acid bacteria, which inhibited the proliferation of undesirable bacteria, such as Hafnia alvei, Enterobacter cloacae, and Serratia proteamaculans. Co-occurrence networks identified 32 nodes with 164 positive and 18 negative correlations in bacteria and 80 nodes with two negative and 76 positive correlations in fungi during fermentation. These results suggested that inclusion of forage legume to grasses can improve the fermentation quality and optimize the structure of microbial community, which appears to be a feasible strategy to enhance the forage resource utilization.